Nano polarimetry: enhanced AFM-NSOM triple-mode polarimeter tip - Karelits, Matityahu (Sci Rep, 2020)
A novel application of a combined and enhanced NSOM-AFM tip-photodetector system resulted in a nanoscale Polarimeter, generated by four different holes, each sharing a different shape, and enabling that the four photonic readouts forming the tip will be the four Stokes coefficients, this in order to place the polarization state in the Poincare sphere. The new system has been built on standard Atomic Force Microscope (AFM) cantilever, in order to serve as a triple-mode scanning system, sharing complementary scanning topography, optical data analysis and polarization states. This new device, which has been designed and simulated using Comsol Multi-Physics software package, consists in a Platinum-Silicon drilled conical photodetector, sharing subwavelength apertures, and has been processed using advanced nanotechnology tools on a commercial silicon cantilever. After a comparison study of drilled versus filled tips advantages, and of several optics phenomena such as interferences, the article presents the added value of multiple-apertures scanning tip for nano-polarimetry.